1999
DOI: 10.1159/000008617
|View full text |Cite
|
Sign up to set email alerts
|

Early Hemodynamic Changes during Uncontrolled Intra-Abdominal Bleeding

Abstract: Central hemodynamics was studied in 32 pigs during the first 10 min after making a 5-mm laceration in the infrarenal aorta. Blood flow probes were placed proximally and distally to the site of the bleeding and also over the portal vein and renal artery. We found that the bleeding, which was indicated by a difference in the rate of blood flow between the two aortic probes, stopped spontaneously after about 3 min. The short-term changes in blood flow rates closely followed simple monoexponential functions with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Different treatment groups were confirmed to be comparable before the randomization by ANOVA in our series. We observed a protracted hemorrhage lasting 6 to 7 min, compared to former studies on uncontrolled hemorrhages from the abdominal aorta where the bleeding stopped at approximately 3 min after injury [11,28]. The prolonged bleeding time may also be explained by the venous incapacity of vasoconstriction.…”
Section: Discussionsupporting
confidence: 41%
“…Different treatment groups were confirmed to be comparable before the randomization by ANOVA in our series. We observed a protracted hemorrhage lasting 6 to 7 min, compared to former studies on uncontrolled hemorrhages from the abdominal aorta where the bleeding stopped at approximately 3 min after injury [11,28]. The prolonged bleeding time may also be explained by the venous incapacity of vasoconstriction.…”
Section: Discussionsupporting
confidence: 41%
“…Injury to a large blood vessel results in the formation of a thrombus that adheres to the outer surface of the vessel and the surrounding tissue. 29,30 In pigs, this immature clot arrests the hemorrhage within 4 min in the aorta, 4,5,15,16 while liver injury might require twice as long time. 31 However, mechanical and chemical forces can apparently disturb stabilization of the clot.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The double flow probe method showed that the rate of the initial hemorrhage decreased in an exponential manner and stopped completely within 4 minutes (half-time 40 seconds) in a pig weighing 20 kg 4 (Fig. 2).…”
Section: Studies In Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one prior model has demonstrated the timing of hemorrhage cessation. 27,28 In that study spontaneous cessation of hemorrhage occurred 3 minutes after a 5-mm laceration was created in the abdominal aorta of a swine model. We suggest that discrepancies in the timing of spontaneous cessation of hemorrhage between these two models were due to two factors.…”
Section: Discussionmentioning
confidence: 99%